Outcomes of salvage hip surgery in children with cerebral palsy. Issue 4 (July 2019) - Chan, Priscella; Hsu, Angela; Godfrey, Jenna; Silva, Selina S.; Goldstein, Rachel Y.; Ryan, Deirdre; Choi, Paul D.; Kay, Robert M.
Abstract : This study compared the outcomes of four salvage procedures in treating painful dislocated hips in patients with cerebral palsy: Schanz osteotomy, Girdlestone, Castle, and McHale procedures. A retrospective review of cerebral palsy patients treated between 1990 and 2014 with minimum 6-month follow-up was carried out. Of 69 hips (62 patients), there were 36 McHales, 24 Castles, four Girdlestones, and five Schanz procedures at a mean age of 13.9 years. All four procedures provided pain relief. Proximal femoral migration was similar following the procedures, but heterotopic ossification was more common after the Castle procedure. Bone resorption and revision surgery were more frequent after the McHale procedure.